Structural- and optical-properties analysis of single crystalline hematite (α-Fe2O3) nanocubes prepared by one-pot hydrothermal approach - Rashid, N.M.A.; Haw, C.Y.; Chiu, W.S.; Khanis, N.H.; Rohaizad, A.; Khiew, P.S.; Rahman, S.A. (Royal Society of Chemistry, 2016)
High quality single crystal hematite (α-Fe2O3) nanocubes with average dimensions of 40 nm were successfully synthesized by a facile one-pot hydrothermal method. Systematic analyses were performed to investigate the morphological-, structural- and optical-properties of the as-synthesized α-Fe2O3 nanocubes. Continuous formation and hourly monitoring towards proper arrangement of single crystal α-Fe2O3 nanocubes was observed throughout the hydrothermal heating process of 180 °C from 4 h to 12 h. The probable growth mechanism on the formation of cubic nanostructures is also proposed. Electron micrographs show the cubic α-Fe2O3 synthesized at the most optimum 8 h hydrothermal heating duration are indeed produced in high-yield with a well-defined cubical shape. The typical rhombohedral structure of cubic α-Fe2O3 was evident from the XRD pattern. The SAED pattern indicates that the α-Fe2O3 nanocubes are single-crystalline in nature, with lattice-fringes and a d-spacing value of 3.6 Å. The optical characterization reveals that α-Fe2O3 nanocubes show strong visible-light absorption with a band gap energy of ∼2.1 eV while the photoluminescence emission spectra depicts a mono-peak centered at ∼590 nm. Both the SAED pattern and UV-vis spectra show a strong correlation with the standard α-Fe2O3. The as-synthesized α-Fe2O3 single crystal is of high quality that potentially could be used as a visible-light active nanomaterial in renewable energy device applications.